Peran Puskesmas dalam Pengembangan Desa Siaga di Kabupaten Bantul - Lucia Sri Rejeki; Mubasysyir Hasanbasri; Guardian Yoki Sanjaya (Center for Health Policy and Management, 2012)
Health Center’s Role Alert Village’s Development in Bantul RegencyBackground: Alert village is a village where the residents have the readiness of resources, the ability, and the intention to independently prevent and overcome health problems or threats, disaster, and emergency. Health center has a duty as the facilitator of the alert village’s development, where besides providing basic medical care, health center is expected to be able to carry out the mobilization and the community empowerment. If the facilitation process succeeded, it can evoke intentions and community independence in health, so that alert village’s liveliness comes from community’s initiative and is not from health center. This kind of development strategy leads to community development. Objective: This research aims to review the role of health center within alert village’s development, especially towards the facilitation of alert village’s development. Method: This research uses the qualitative descriptive method along with a case study design, to describe health center’s perception towards alert village’s development and health center’s role as the alert village’s facilitator. The subjects of this research are the heads of health centers and midwife coordinators, as well as the community leaders: the heads of the public’s welfare affair and the chief of village’s women organization. The datas are collected through in-depth interviews. Results: This research showed various activities of Community-Based Health Efforts as the form of alert village’s implementation. The facilitation which health center provides to actualize active alert village had not showed community development, but rather a social mobilization. The obstructions are that health center has not been provided with facilitation techniques and the community’s culture is less independent in health. Conclusion: Alert village’s development towards community development has not been utterly well responded by the community.Keywords: Facilitation, Alert village, Community development.Latar Belakang: Pengembangan masyarakat menjadi salah satu topik yang paling populer didalam konteks intervensi ke- sehatan masyarakat. Di Indonesia, Desa Siaga merupakan ben- tuk pengembangan masyarakat di bidang kesehatan. Desa Sia- ga adalah desa yang penduduknya memiliki kesiapan sumber- daya dan kemampuan serta kemauan untuk mencegah dan mengatasi masalah/ancaman kesehatan, bencana dan kega- watdaruratan secara mandiri. Puskesmas memiliki tugas seba- gai fasilitator pengembangan desa siaga, dimana selain mem- berikan pelayanan medis dasar, diharapkan mampu melaksana- kan tugas penggerakan dan pemberdayaan masyarakat. Fasili- tasi pengembangan desa siaga ini tergantung kemampuan pus- kesmas, disini diharapkan puskesmas mampu menerapkan prin- sip-prinsip fasilitasi yang efektif. Apabila proses fasilitasi ber- hasil akan menumbuhkan kemauan dan kemandirian masya- rakat di bidang kesehatan, sehingga keaktifan desa siaga ber- asal dari inisiatif masyarakat bukan dari puskesmas. Fasilitasi pengembangan seperti ini mengarah pada community devel- opment. Tujuan: Penelitian ini bertujuan untuk melakukan kajian terha- dap peran puskesmas dalam fasilitasi pengembangan desa siaga. Metode: Penelitian ini menggunakan metode deskriptif kualitatif dengan rancangan studi kasus, untuk mendeskripsikan peran puskesmas sebagai fasilitator desa siaga. Subyek penelitian adalah kepala puskesmas dan bidan koordinator, serta tokoh masyarakat : kepala bagian kesejahteraan rakyat desa, ketua Tim Penggerak PKK desa, dan kader kesehatan. Data dikumpul- kan melalui wawancara mendalam dan observasi. Hasil: Desa siaga telah dilaksanakan dengan berbagai kegiatan Upaya Kesehatan Bersumberdaya Masyarakat (UKBM), namun belum semuanya berjalan seperti yang diharapkan. Puskesmas telah berupaya dalam mendampingi pengembangan desa siaga, namun fasilitasi yang dilakukan puskesmas belum mewujudkan community development, melainkan lebih kearah mobilisasi sosial. Kesimpulan: Pengembangan desa siaga kearah community development belum terwujud dalam masyarakat.Kata Kunci : Fasilitasi, Desa siaga, Community development.